Política antigua - política moderna - Javier Fernández Sebastián (Mélanges de la Casa de Velázquez)
This article presents some considerations regarding the general theme of the volume —the onset of modern politics in Spain— from the standpoint of cultural and intellectual history, with particular reference to language. Following a critique of some very common historiographic dichotomies relating to revolutions, for instance continuity versus rupture, survivals versus innovations or tradition versus modernity, the author posits the desirability of utilising some of the theoretical tools that conceptual history offers to solve such contradictions as a means to arrive at a fuller, more nuanced vision of the transition between historical concepts, discourses, identities and actors in the hundred years from the mid-18th to the mid-19th century. He pays particular attention to asynchronicity and the multiplicity of time-frames relating to the various different sectors and levels of historical change; and he also stresses the need at all cost to avoid a kind of anachronism consisting in the back-projection of political and social categories proper to the 20th century on to earlier eras and the attribution to past populations of concepts, aspirations or ways of seeing the world that were completely alien to them.